(untitled) (Research, Society and Development, 2021)
The aim of this work was to study urban solid waste from grass pruning (RSPG) at District of Primavera, in Rosana-SP, using gravimetric and calorimetric methods to evaluate the feasibility of using it as an energy source in direct combustion processes. RSPG samples were collected, washed, dried in air for 24h, fractionated in a knife mill and selected in a granulometric sieve before gravimetric and calorimetric analyses. Analyzes of moisture, total solids, aqueous and alcoholic extractives, ash, structural and non-structural inorganics, total inorganics, and higher heating value (HHV) were carried out. The aqueous and alcoholic extraction processes were carried out in an ultrasonic bath and presented values of 14.32 ± 0.28% for aqueous extractives and 6.65 ± 0.40% for alcoholic extracts. The samples showed values of structural inorganics and non-structural inorganics of 2.97±0.17% and 1.26±0.12%, respectively. RSPG proved to be an alternative as solid fuel by presenting a HHV value of 17.59±0.43 MJ kg-1 which is like other solid wastes.